2014
DOI: 10.1002/ana.24131
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of inherited manganese transporter deficiency

Abstract: We followed a patient with manganese transporter deficiency due to homozygous SLC30A10 mutations from age 14 years until his death at age 38 years and present the first postmortem findings of this disorder. The basal ganglia showed neuronal loss, rhodanine-positive deposits, astrocytosis, myelin loss, and spongiosis. SLC30A10 protein was reduced in residual basal ganglia neurons. Depigmentation of the substantia nigra and other brainstem nuclei was present. Manganese content of basal ganglia and liver was incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 17 publications
0
61
0
Order By: Relevance
“…These authors followed the patient described in their report from the age of 14 till death at age 38, and then described autopsy findings in a second manuscript (Lechpammer et al . ). The patient had homozygous mutations in SLC30A10 (Tuschl et al .…”
Section: Manganese Exportmentioning
confidence: 97%
See 1 more Smart Citation
“…These authors followed the patient described in their report from the age of 14 till death at age 38, and then described autopsy findings in a second manuscript (Lechpammer et al . ). The patient had homozygous mutations in SLC30A10 (Tuschl et al .…”
Section: Manganese Exportmentioning
confidence: 97%
“…; Lechpammer et al . ). Important features observed during autopsy included severe neuronal loss in the basal ganglia, particularly in the globus pallidus, along with a 16‐fold increase in basal ganglia and a 9‐fold increase in liver Mn levels (Lechpammer et al .…”
Section: Manganese Exportmentioning
confidence: 97%
“…A Tf-dependent mechanism for Mn transport in rat PC12 cells has been described before. 107 Recently, Gunter and colleagues have developed an approach to study the Tf-dependent Mn transport independently of other Mn transport mechanisms. Using mouse hippocampal (HT22) and striatal (STHdhQ7/Q7) neurons, they have demonstrated that Mn can be conjugated to Tf when in the Mn 3+ state and then be transported into neurons via the Tf receptor (TfR) analogously to Fe 3+ .…”
Section: Mn Transporters: Regulation Of Mn Levelsmentioning
confidence: 99%
“…Several recent clinical studies have reported that human subjects with Solute Carrier Family 30 Member 10 (SLC30A10; ZnT10) deficiency/mutation display higher Mn accumulation in the liver 67 and blood 103, 104 , as well as 10 times higher Mn in the basal ganglia, which is associated with dystonia, a typical phenotype of Mn neurotoxicity 105107 . SLC30A10 was thought to be a zinc exporter, but its amino acid structure is different from other zinc transporters in this family 108 , and it was later suggested that SLC30A10 may not be involved in zinc transport 109 .…”
Section: Introductionmentioning
confidence: 99%